2020
DOI: 10.1016/j.molcel.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Kinase Interaction Network Expands Functional and Disease Roles of Human Kinases

Abstract: Summary Protein kinases are essential for signal transduction and control of most cellular processes, including metabolism, membrane transport, motility, and cell cycle. Despite the critical role of kinases in cells and their strong association with diseases, good coverage of their interactions is available for only a fraction of the 535 human kinases. Here, we present a comprehensive mass-spectrometry-based analysis of a human kinase interaction network covering more than 300 kinases. The interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 107 publications
4
92
0
Order By: Relevance
“…In further support of these interrelations, the number of 14-3-3 prey-binding baits also indicated correlation with the affinity trend of 14-3-3 isoforms when using data from a recent independent study ( https://sec-explorer.shinyapps.io/Kinome_interactions/ and 49 ) that used AP-MS to uncover the interactions of more than 300 protein kinases ( R 2 = 0.64) (Supplementary Fig. 7a ).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…In further support of these interrelations, the number of 14-3-3 prey-binding baits also indicated correlation with the affinity trend of 14-3-3 isoforms when using data from a recent independent study ( https://sec-explorer.shinyapps.io/Kinome_interactions/ and 49 ) that used AP-MS to uncover the interactions of more than 300 protein kinases ( R 2 = 0.64) (Supplementary Fig. 7a ).…”
Section: Resultsmentioning
confidence: 62%
“…Conversely, the seven 14-3-3 isoforms bound each E6 phosphopeptide following a conserved hierarchized profile, with an approximate 11-fold K D ratio between the strongest-binding and the weakest-binding 14-3-3 isoform. Remarkably, 14-3-3 proteins obey the same hierarchy when binding to most of their targets, as supported by our own data on RSK1 and HSPB6 peptides, by our literature curation 40 , 44 48 , and by the unbiased proteome-wide complexome datasets such as the BioPlex 3 database ( https://bioplex.hms.harvard.edu and 29 ) or the human kinome interactome ( https://sec-explorer.shinyapps.io/Kinome_interactions/ and 49 ). Only 14-3-3σ may stand out as a partial exception to this rule.…”
Section: Discussionmentioning
confidence: 61%
“…Among the effective combinations identified from this screen, we found that a novel combination, pairing the CK2 inhibitor CX-4945 with the ATM inhibitor KU-60019, dramatically enhanced cell death in VHL-deficient renal carcinoma cells. CK2 has effects on a broad range of cellular functions participating to the (DDR) [ 98 ] and to the regulation of chromatin modifiers [ 99 , 100 , 101 , 102 , 103 ]. More specifically, its implication in tumor development and recurrence may be related to its double-edge functions in promoting cell growth and inhibiting apoptotic cell death [ 104 ] and in the development of multidrug resistance phenotypes [ 35 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advances in high‐accuracy mass spectrometry has led proteomics to be a powerful tool for unveiling complex protein network in cells 47 . Researchers generally use the total proteome or phospho‐proteome to extract disease‐related protein networks, such as explored here for EGFR‐mutant NSCLC 48,49 . Recently, Nishimura et al analyzed 36 FFPE tissues of lung adenocarcinomas using semi‐quantitative shotgun proteomics.…”
Section: Discussionmentioning
confidence: 99%